DS+ meson production at central rapidity in proton-proton collisions at √s=7 TeV - Abelev, B.; Adam, J.; Adamova, D.; Adare, A. M.; Aggarwal, M. M.; Rinella, G. Aglieri; Agocs, A. G.; Agostinelli, A.; Salazar, S. Aguilar; Ahammed, Z.; Ahmad, N.; Masoodi, A. Ahmad; et al. (ELSEVIER, 2012)
The P-T-differential inclusive production cross section of the prompt charm-strange meson D-s(+) in the rapidity range vertical bar y vertical bar phi pi(+) with phi -> K-K+, and its charge conjugate, about 480 D-s(+/-) mesons were counted, after selection cuts, in the transverse momentum range 2 < P-T < 12 GeV/c. The results are compared with predictions from models based on perturbative QCD. The ratios of the cross sections of four D meson species (namely D-0, D+, D*+ and D-s(+)) were determined both as a function of p(T) and integrated over p(T)after extrapolating to full p(T) range, together with the strangeness suppression factor in charm fragmentation. The obtained values are found to be compatible within uncertainties with those measured by other experiments in e(+)e(-), ep and pp interactions at various centre-of-mass energies. (C) 2012 CERN. Published by Elsevier By. All rights reserved.
Keywords: THERMAL HADRON-PRODUCTION; STATISTICAL HADRONIZATION; INCLUSIVE PRODUCTION; CHARM PRODUCTION; B-DECAYS; HEAVY; FRAGMENTATION; QUARKS; D+; Astronomy & Astrophysics; Physics